2006
DOI: 10.1111/j.1365-2265.2006.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian hydrocortisone infusions in patients with adrenal insufficiency and congenital adrenal hyperplasia

Abstract: In patients with poor biochemical control of Addison's disease and CAH, a 24-h circadian infusion of hydrocortisone can decrease morning ACTH and 17-hydroxyprogesterone levels to near normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 19 publications
3
61
0
Order By: Relevance
“…1). In the patients with CAH, very high plasma ACTH and 17-hydroxyprogesterone levels were present before the morning dose and at the end of conventional HC treatment, in contrast to significantly lower levels of both ACTH and 17-hydroxyprogesterone after circadian infusion (17) (Fig. 2).…”
Section: Circadian Hc Infusionsmentioning
confidence: 94%
See 1 more Smart Citation
“…1). In the patients with CAH, very high plasma ACTH and 17-hydroxyprogesterone levels were present before the morning dose and at the end of conventional HC treatment, in contrast to significantly lower levels of both ACTH and 17-hydroxyprogesterone after circadian infusion (17) (Fig. 2).…”
Section: Circadian Hc Infusionsmentioning
confidence: 94%
“…Moreover, monitoring treatment remains a challenge, and is based on clinical assessment and biochemical parameters (12)(13)(14). Recently, efforts have focused on the development of newer formulations of HC to provide circadian glucocorticoid replacement therapy aimed to imitate more closely the normal physiological cortisol rhythm (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, patients with congenital adrenal hyperplasia (CAH) receive suppression treatment with long-acting glucocorticoids, which is limited by the risk of glucocorticoid over-dosage. Recently, a small clinical study found that circadian HC infusions in patients with CAH and AD improved biochemical control as measured by ACTH and 17-OH-progesterone (15). CSHI may be a means to Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…A potential drawback of this type of monitoring is that high plasma ACTH levels are found in patients with primary adrenal insufficiency without pituitary pathology. In patients with Addison's disease plasma ACTH measured before morning glucocorticoid is frequently very elevated, but this suppresses rapidly 120 minutes after morning glucocorticoid (20,21). In contrast, those with Nelson's syndrome fail to show incomplete suppression, and a cut-point of 200 pg/ml appears to be useful to define Nelson's syndrome (12).…”
Section: Monitoringmentioning
confidence: 99%